The Effect Of Organizational Citizenship Behavior (OCB) and Organizational Commitment on Employee Performancewith Workload as a Intervention Variable at BPJS Ketenagakerjaan South Sumatra Regional - Komang Mustiawan; Hernawaty (Equivalent : Journal of Economic, Accounting and Management, 2026)
This study aims to examine the influence of Organizational Citizenship Behavior (OCB) and organizational commitment on employee performance with workload as an intervening variable at the BPJS Ketenagakerjaan South Sumatera Regional Office.This study used a quantitative approach with a survey method. The sample consisted of 70 employees selected through a saturated sampling technique. Data were collected using a questionnaire and analyzed using the Structural Equation Modeling–Partial Least Square (SEM-PLS) method. The results of the study indicate that Organizational Citizenship Behavior (OCB) and organizational commitment have a positive and significant influence on employee performance. Furthermore, OCB and organizational commitment have a negative and significant influence on workload. Workload is proven to have a negative and significant influence on employee performance. The indirect effect analysis shows that workload mediates the relationship between Organizational Citizenship Behavior and organizational commitment on employee performance. Therefore, strengthening OCB, increasing organizational commitment, and managing workload effectively are crucial to improving employee performance.